2021
DOI: 10.1063/5.0058044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphene domains orientation on quasi van der Waals epitaxy of GaN

Abstract: We demonstrate the growth features of III-nitrides on graphene buffer layers obtained by the CVD method on a copper catalyst with different dominant grain orientations. The reflection high-energy electron diffraction technique (RHEED) is used to map the 2D reciprocal space structures of graphene buffers and growing nitride layers. The RHEED reciprocal space pattern for the graphene layer grown on a (111) textured copper foil and transferred to a SiO2/Si substrate demonstrates the sixfold symmetry characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…In the reciprocal space, the radius and polar angle correspond to the reciprocal distance from the (00) spot and azimuthal angle, respectively. Figure 4b,e shows the intensity profiles of line scans as a function of k|| (the distances from (hk) to (00)) at a fixed value k⊥ [28,65]. Since a sample with FLG is more characterized by SLG regions, the widened peaks characteristic of graphene are noticeable in the RHEED images (Figure 4a-c).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the reciprocal space, the radius and polar angle correspond to the reciprocal distance from the (00) spot and azimuthal angle, respectively. Figure 4b,e shows the intensity profiles of line scans as a function of k|| (the distances from (hk) to (00)) at a fixed value k⊥ [28,65]. Since a sample with FLG is more characterized by SLG regions, the widened peaks characteristic of graphene are noticeable in the RHEED images (Figure 4a-c).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown [28,65,66], the RHEED technique can be applied for visualization of graphene reciprocal structure and to analyze the ordering of its crystalline domains. Previously [38], it was shown that in the case of a single-crystal 2D material, its reciprocal space structure consists of vertical rods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations